Co, N-Doped TiO2 Coated r-GO as a photo catalyst for Enhanced photo catalytic Activity. (2017) - Murthy, M.; Tubaki, Suresh; Lokesh, S.V.; Rangappa, Dinesh
Abstract: A highly efficient Cobalt(Co) and Nitrogen (N) doped TiO2 /Reduced Graphene oxide(RGO) hybrid nano catalyst was synthesized by sol-gel and hydrothermal method. The Co, N-doped/RGO (CNDTR) hybrid catalyst shows enhanced visible light photocatalytic degradation of methylene blue dye. The average particle size of the Co, N-doped TiO2 /RGO (CNDTR) catalyst is about 25 nm. The morphology of the samples observed indicates irregular shaped particles deposited on the graphene sheets. The photo catalytic activities of the samples were evaluated through photo degradation Methylene blue dye under visible light irradiation. Doping of Co and N cause the red shift of the absorption onset of TiO2 to the visible region and enhance the photo catalytic activity. Compared with the Co, N-doped TiO2 (CNDT) sample Co, N -Doped TiO2 /RGO(CNDTR) exhibited the highest photocatalytic activity, This can be ascribed to the synergistic effect of the N and Co co-doping along with increased surface area of the samples due to RGO.